(untitled) (Homoeopathy for All, 2023)
Polycystic ovarian syndrome (PCOS) is a prevalent endocrine disorder affecting reproductive-aged women worldwide, characterized by hormonal imbalances, irregular menstrual cycles, ovarian cysts, and various metabolic disturbances, hyperandrogenism, ovulatory dysfunction, and polycystic ovarian morphology.1 Over the past couple of years, the world has been grappling with the devastating effects of the COVID-19 pandemic caused by the novel coronavirus, SARS CoV-2. While the primary impact of COVID-19 is respiratory, emerging evidence suggests that the virus can have wide-ranging effects on other organ systems, including the endocrine system. When we examine its effects on the female endocrine system, it results in menstrual irregularities, hormonal imbalances, fertility issues, etc. Apart from its direct effects, even the use of COVID-19 vaccine is also reported to influence the menstrual cycle length, flow, duration of menstruation, symptoms, and abnormal bleeding without an effect on post-menopausal vaginal bleeding.2 All these may possibly end up in PCOS due to multiple factors, including hormonal imbalance, stress, and others. Researchers have also traced its possible mechanism to be related to the increased androgen activity, which make the body vulnerable to infections.